Urgent Choices: Evaluating The Impact of Housing and Wash Programs in Indonesia - Hanri, Muhammad; Dewi, Calista Endrina; Puspita, Sheny Diah (Journal of Developing Economies, 2025)
This study evaluates the impact of Indonesian government programs in the housing and water, sanitation, and hygiene (WASH) sectors on social welfare, specifically targeting poverty reduction and health improvement. The primary hypothesis is that enhanced progress in housing and WASH programs correlates with lower poverty rates and improved health outcomes. Using data from SUSENAS and the Ministry of Development Planning, we employ a fixed effects model to mitigate endogeneity concerns and accurately assess program impact. Findings reveal that while advancements in WASH programs are significantly associated with improved public health, no strong evidence links these programs to poverty reduction. The study recommends prioritizing WASH program expansion and refining housing program strategies to address health outcomes more effectively and promote targeted poverty alleviation measures. These recommendations offer insights into optimizing development programs to enhance Indonesia’s socio-economic landscape.